“Just having experience is not enough”: development and evaluation of a training for interpreters working in community settings – a mixed-methods study - Hanft-Robert, Saskia; Breitsprecher, Christoph; Mösko, Mike (Frontiers in Education, 2025)
BackgroundAcross community settings, such as healthcare, interpreters play an important role in facilitating communication when service users and providers do not share a common language sufficiently. Because most countries lack legal standards in the field of Community Interpreting, Community Interpreters (CIPs) are often not adequately trained for this activity, and the need for formal training is increasingly emphasized. This study aims to evaluate a generic training for CIPs in Germany.MethodsThe training was developed for interpreters working in health and social care, education, and authorities in Germany. It consists of 500 units and a final examination. A mixed-methods design was applied to evaluate the training. Training participants’ (TPs) satisfaction, knowledge, competence, and professional self-efficacy expectations were measured by self-developed questionnaires. A pre-post multiple-choice knowledge test was developed to objectively assess the trainings’ impact on knowledge. Qualitative pre- and post-interviews were conducted for an in-depth evaluation of TPs’ motives for participating in the training, their experiences, improvements in knowledge and skills as well as their attitude changes. Trainers’ qualifications and satisfaction were assessed using self-developed questionnaires. Quantitative data were analyzed descriptively, and qualitative data were analyzed using a content analysis approach.ResultsIn total, n = 21 TPs and n = 18 trainers were included. Quantitative analysis revealed that trainers and TPs were overall satisfied with the training. TPs showed increased subjective and objective knowledge, competence, and professional self-efficacy expectations. Qualitative findings revealed changes in TPs’ knowledge about their role and ethical principles; they reported increased skills and confidence on both professional and personal levels. Due to the training, their interpreting performance changed from being relatively intuitive and “natural” to being informed and skills-based. They recognized the complexity of interpreting, thereby acknowledging their professional status. Obtaining a certificate after completing the examination increased their feeling of professionalism. However, TPs expressed the need for further in-depth training, as the training was rather generic and broad.ConclusionThe study demonstrates that generic training can enhance CIPs’ knowledge, skills, competence, professional and personal confidence, and perceived professionalism. It highlights the critical need for formalized training, certification, and overall qualification programs to ensure not only the quality of interpreting services but also to shape the profession of CIPs.